PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP KOMUNIKASI WORD OF MOUTH - Mertayasa, Putu; Giantari, I Gusti Ayu Ketut (Buletin Studi Ekonomi, 2020)
The purpose of this study was to explain the effect of product quality and brand image on IndiHome customer satisfaction in Denpasar City, and to explain the effect of product quality, brand image and customer satisfaction on IndiHome customers' word of mouth communication in Denpasar City. The population in this study were all IndiHome customers in Denpasar City. The sampling technique used is purposive sampling method. The number of samples used in this study were 100 respondents. The data analysis technique used in this study is path analysis. The results showed that product quality and brand image had a positive and significant effect on IndiHome customer satisfaction in Denpasar City, and product quality, brand image and customer satisfaction had a positive and significant effect on IndiHome customers' word of mouth communication in Denpasar City.